MITIGATING RENAL STRESS WITH GREEN TEA EXTRACT IN MICE EXPOSED TO TOBACCO SMOKE - Aldin Akbar Rahmatullah; Adinda Rizky Trisakti; Sucia Nadila; Anggreani Desi Ramadhani Rahajeng (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2026)
Cigarette smoke induces oxidative stress that impairs kidney function, as reflected by increased blood urea nitrogen (BUN) and creatinine levels. Green tea extract (GTE), rich in epigallocatechin gallate (EGCG), is known for its antioxidant properties and potential nephroprotective effects. However, its role in protecting against cigarette smoke-induced renal injury remains unclear. This study aimed to evaluate the protective effect of GTE in a dose-dependent manner using a mouse model. Twenty-five male Mus musculus were divided into five groups: negative control (C−), positive control exposed to cigarette smoke (C+), and three treatment groups receiving GTE at doses of 20, 40, and 60 mg/kg body weight (T1, T2, T3). GTE was administered orally for 36 days, followed by smoke exposure in a controlled chamber. On day 37, serum BUN and creatinine levels were measured. The C+ group showed significantly elevated BUN and creatinine levels compared to the C− group. GTE administration reduced these levels in a dose-dependent manner, with the greatest improvement observed in the T3 group (60 mg/kg), approaching normal values. These findings suggest that GTE effectively mitigates cigarette smoke-induced renal damage and holds promise as a natural nephroprotective agent